Effect of Science Teaching Materials Integrated Blended-PBL Models on Students’ 21st Century Skills: A Meta-Analysis - Dinelti Fitria; Lufri Lufri; Asrizal Asrizal; Aprina Maharani (Jurnal Penelitian Pendidikan IPA, 2023)
The objective of the study was to analyze the effect size of a number of similar studies on students' 21st century skills. The research method can be classified into meta-analysis. In this meta-analysis method, the effect size of each similar study was determined and the hypotheses were tested from a number of similar studies. In this study, 26 similar articles were analyzed from national journals and international journals. As independent variables are science teaching materials, as moderator variables are types of teaching materials, learning models, and level of education. From the results of the analysis, it can be stated that science teaching materials have a positive effect on 21st century skills based on the type of teaching materials, learning models, and educational level. Therefore, the use of science teaching materials is effective for improving students' 21st century skills both in terms of various types of teaching materials, learning models, and educational levels